Experimental characterization of a solar powered MSF desalination process performance. (May 2019) - Darawsheh, I.; Islam, MD.; Banat, F.
Highlights: Flat plate solar collectors integrated with multistage vacuum chambers for desalination. Parametric study has been conducted experimentally. Lowering 20% of atm pressure in chamber, the distillation to evaporation ratio enhance by 53%. Abstract: Desalination technology has become a significant solution of fresh drinking water for many parts of the world. Lack of fresh water resources in dry environments has encouraged the establishment of desalination processes and developed technology to compensate for water scarcity. However, conventional desalination plants rely mainly on using fossil fuels for operating the process, rendering desalination costly and augmenting environmental pollution. For such difficulties, using renewable energy for desalination plants is a beneficial alternative in terms of economical, environmental and sustainability aspects. In this research work, flat plate solar collectors were integrated with multistage vacuum chambers and operated a solar multi stage flash (MSF) desalination facility. An experimental parametric study has been carried out that leads to optimum process performance and cost effective desalination technology. A major finding of this research was that by reducing 20% of atmospheric pressure in a vacuum flash chamber, the distillation to evaporation ratio was enhanced by 53% and specific energy consumption was reduced by 35%. The best distillation to evaporation ratio was 0.42 at a feed flow of 0.5 L/min.